ERRATUM TO: FACTORS RELATED TO DEPRESSION AMONG OLDER PEOPLE LIVING IN CIMAHI, WEST JAVA PROVINCE, INDONESIA - Kiki Gustryanti; Sunanta Thongpat; Sonthaya Maneerat (Belitung Nursing Journal, 2020)
After publication of the article (Gustryanti et al., 2017), it has been brought to our attention that the wrong title was used on initial publication. The correct title of this article is “Factors related to depression among older people living in Cimahi, West Java Province, Indonesia”. The original version of the article has been updated to reflect this. In addition, the reference format in this article has also been updated. The publisher apologizes for the minor errors. The corrected article can be seen in the following doi: https://doi.org/10.33546/bnj.50